I can feel it moving: Science Communicators Talking About the Potential of Mid-Air Haptics - Hajas, Daniel; Ablart, Damien; Schneider, Oliver; Obrist, Marianna (Frontiers in Computer Science, 2020)
We explored the potential of haptics for improving science communication, and discovered the mid-air haptic feedback supports flexible, engaging discussions in a way that other technologies, like 3D printed models and VR headsets, may not. While science instruction often focuses on the cognitive domain of acquiring new knowledge, in science communication the primary goal is to produce personal responses, such as awareness, enjoyment, or interest in science. Science communicators often use new technologies to produce personal responses. Here, we explore how mid-air haptics technology could play a role in communicating scientific concepts. We prototyped six mid-air haptic probes for three thematic areas (i.e. particle physics, quantum mechanics, cell biology) and conducted three workshops with domain experts who are also active science communicators. Participants were impressed by the dynamic features of mid-air haptics, its ability to produce shared experiences, and its flexibility in communicating scientific concepts. We discuss how mid-air haptics can complement existing approaches (e.g. 3D printing, virtual reality) and help create enjoyment, interest, and maybe understanding in science